Pengaruh Komunikasi Interpersonal dan Kualitas Jasa terhadap Kepuasan Pelanggan Pelayanan Aplikasi Visa Australia Di PT Andalan Usaha Cemerlang Jakarta Timur - Denny Suriandhi (UniSadhuGuna Business School, 2019)
PT Andalan Usaha Cemerlang is the organization who consider about customer satisfaction. And give quality of interpersonal communication and quality of service. Both of variable have a significant and simultaneous to customers satisfaction with associative quantitative method discovered that both of variable have a coefficient determinant R2 = 0.827 or 82,8% and the rest of amount is 17.2% because of the other factors. Suggestion to PT Andalan Usaha Cemerlang is all quality service and interpersonal communication must be maintained and improved to keep customers’loyality.